Human Rights and Public Freedoms in the Palestinian Basic Law - Diaa Nader Awad (International Journal of Law Research and Studies, 2025)
Purpose: The study aimed to determine whether the Palestinian political system is democratic by examining the extent to which public rights and freedoms are stipulated in the Amended Palestinian Basic Law of 2003 and its amendments. In addition, this study aimed to address any shortcomings or omissions related to the stipulation of these rights and freedoms, thus contributing to their protection, implementation, and promotion. Methodology: In this study, the researcher used the descriptive, analytical, comparative approach, by describing the extent of the State of Palestine’s interest in public rights and freedoms, whether through stipulating them in the Amended Palestinian Basic Law of 2003 and its amendments or through its accession to major human rights treaties. In addition, the researcher analyzed the texts of this Basic Law that include provisions on human rights and public freedoms, and compared them with those contained in the basic international human rights agreements. Findings: The study concluded that the Amended Palestinian Basic Law followed the approach of democratic constitutions, which have come to be called (Constitutions of the Bill of Rights), by devoting an entire chapter to stipulating human rights and public freedoms. However, it neglected to stipulate crucial general rights and freedoms, namely: the right to life, the right to legal personality, the right to self-determination, the right to sovereignty over natural resources, the prohibition of slavery and servitude, the rights of minorities, the right to possess the common human heritage of humanity, the right to peace, the right to development, the right to health care, the right to access information, and the right to exploit the high seas. Palestine has also acceded to several fundamental international conventions that support and enhance the protection of human rights. Recommendations: The study recommends amending the Amended Palestinian Basic Law to include in its provisions the general rights and freedoms that it neglected to regulate. It also emphasizes the harmonization of Palestinian legislation with the international human rights conventions to which Palestine has acceded.